Student Motivations in Choosing Bachelor of Science in Hospitality Management - Velasco, Joyce Irene R.; Samonte, Charles Darwin C.; Fabian, Jayson L. (Journal of Advanced Research in Education, 2025)
This study explores student motivations in choosing the Bachelor of Science in Hospitality Management. Utilizing a quantitative research design, data were gathered through an adapted structured survey questionnaire from the study of Ouano et al. (2019). The survey was encoded in Google Forms and distributed to 180 first-year students enrolled in the program at Northeastern College, Santiago City, Isabela, selected through purposive sampling. The findings reveal that the majority of respondents were teenagers aged 17-19, with 63% being female and mostly graduates of the HUMMS strand in Senior High School. Additionally, 68% of respondents come from low-income families. The study concludes that four main factors significantly influence students’ motivation to choose the program: knowledge of future job opportunities in the hospitality and tourism industry, personal interest, passion, and the institution’s reputation for producing proficient graduates. Although peer influence is present, it is the least motivator in the decision-making process.